The Little Green Data Book 2011 - World Bank (World Bank, 2012)
This year's edition introduces a new green national accounting aggregate, adjusted Net National Income (aNNI), into the set of environment and development indicators. Using the underlying methodology of the Adjusted Net Saving (ANS) measure, which has been published since the first edition in 2000, aNNI provides a broader measure of national income that accounts for the depletion of natural resources. The standard measure of income in the United Nations System of National Accounts (SNA) is Net National Income (NNI), defined as Gross National Income (GNI) minus depreciation of fixed capital. aNNI starts with NNI, and then subtracts a charge for the depletion of energy, mineral and forest resources, reflecting the decline in asset values associated with their extraction and harvest, this is analogous to depreciation of fixed assets.